Enterotoxigenic Escherichia coli Infections in Newborn Calves: A Review - Acres, Stephen D. (J Dairy Sci, 1985)
Diarrhea caused by enterotoxigenic Escherichia coli is an infectious bacterial disease of calves that occurs during the first few days of life. The Escherichia coli that cause the disease possess special attributes of virulence that allow them to colonize the small intestine and produce an enterotoxin that causes hypersecretion of fluid into the intestinal lumen. These enterotoxigenic Escherichia coli are shed into the environment by infected animals in the herd and are ingested by newborn calves soon after birth. There is some natural immunity to enterotoxigenic Escherichia coli, however, it often fails to protect calves born and raised under modern husbandry conditions. Hence, methods have been developed to stimulate protective immunity by vaccination of the dam. The protective antibodies are transferred passively to calves through the colostrum.